HARMONISATION OF TRAINING BACHELOR’S DEGREE STUDENTS IN ACADEMIC PROGRAMME “PEDAGOGICAL EDUCATION” - Gennady I. Sarantsev (Интеграция образования, 2016)
Introduction: the analysis of bachelor’s training objectives in “Pedagogical Education”, formulated by the Federal Educational Standards (FES), brings to the conclusion that there is a mismatch between them. Achiev- ing one assumes fundamentalisation of teacher’s education, and the other - the improvement of its practical orientation. The research reveals that teacher’s education component corresponds to the development of relevant scientific field. Proposed measures to achieve these goals are often in opposition to the components of teacher’s education. Since the training of students in all activities specified by FES, is carried out in a single educational process, there is a necessity to search for means that eliminate this mismatch, i.e., harmonise teacher’s education. Materials and Methods: a number of studies is concerned with identifying the content of fundamental and practical aspect of training Bachelor’s degree students. Fundamentalisation is strengthening the role of teaching methodology, in particular the methods of research, construction of training courses based on the computerised simulation, systems analysis and activity approach. The practical orientation of education is to form students’ skills based on theoretical and methodological knowledge and universal educational actions. Results: modern methodological thinking serves a basis of harmonisation that embodies a number of profes- sional competence of a teacher extended on the fundamentalisation of education, and on a practical orientation as well. Searching for means of harmonisation of fundamentality and practical orientation of Bachelors training leads to the conclusion that among effective means are tasks that simulate real learning situations, a business game, its simulation, training projects, classes where the experiment is carried out. From the perspective of harmonisation of Bachelors training the author identifies requirements to lecturing and conducting workshops. Discussion and Conclusions: the paper summarises the implementation of the theory of harmonisation of Bachelors training in “Pedagogical education”; presents samples of lectures and workshops that meet the requirement of that harmonisation.